log(12)(x - 3) - log(x-2)(x - 5) + 1/log(x-5)12 ≥ log(x-2)(x - 3).
{x-3>0
{x-5>0
{x-2>0
{x-2 ≠ 1
{x-5 ≠ 1
x ∈ (5;6)U(6:+ ∞ )
применяем формулу перехода к другому основанию:
[m]log_{12}(x-3)+log_{12}(x-5) ≥ log_{x-2}(x-5)+log_{x-2}(x-3)[/m]
[m]log_{12}(x-3)(x-5) ≥ log_{x-2}(x-5)(x-3)[/m]
применяем формулу перехода к другому основанию:
[m]log_{12}(x-3)(x-5) ≥ \frac{log_{12}(x-5)(x-3)}{log_{12}(x-2)}[/m]
[m]log_{12}(x-3)(x-5) - \frac{log_{12}(x-5)(x-3)}{log_{12}(x-2)} ≥ 0[/m]
[m]log_{12}(x-3)(x-5)\cdot (1 - \frac{1}{log_{12}(x-2)}) ≥ 0[/m]
[m]log_{12}(x-3)(x-5)\cdot \frac{log_{12}(x-2)-1}{log_{12}(x-2)} ≥ 0[/m]
Применяем [i]обобщенный[/i] метод интервалов:
[m]log_{12}(x-3)(x-5)=0[/m]
[m](x-3)(x-5)=1[/m]
[m]x^2-8x-14=0[/m] ⇒[b] x=4 ± sqrt(2)[/b]
[m]log_{12}(x-2)-1=0[/m] ⇒ x-2=12; [b]x=14[/b]
[m]log_{12}(x-2) = 0[/m] ⇒ x=1
(5)_-__ [4+sqrt(2)] _[red]+[/red]__ (6) __-__ [14] _[red]+[/red]_
[4+sqrt(2);6)U[14;+ ∞ )